2006
DOI: 10.1093/rheumatology/kei221
|View full text |Cite
|
Sign up to set email alerts
|

In SAPHO syndrome anti-TNF-α therapy may induce persistent amelioration of osteoarticular complaints, but may exacerbate cutaneous manifestations

Abstract: Infliximab seems to be a very effective therapy for osteoarticular complaints of SAPHO syndrome. Cutaneous involvement responded less favourably, palmoplantaris pustulosis relapse being a possible complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(56 citation statements)
references
References 22 publications
2
43
0
11
Order By: Relevance
“…It was demonstrated that the use of tumor necrosis factor inhibitors leads to favorable clinical outcomes in patients with SAPHO syndrome. 15,16 Similarly, clinical remission was obtained under etanercept in our patient.…”
Section: Discussionsupporting
confidence: 75%
“…It was demonstrated that the use of tumor necrosis factor inhibitors leads to favorable clinical outcomes in patients with SAPHO syndrome. 15,16 Similarly, clinical remission was obtained under etanercept in our patient.…”
Section: Discussionsupporting
confidence: 75%
“…Our patient experienced a temporary aggravation of cutaneous lesions, which is in accordance with other authors' findings [8]. The aggravation is probably a side effect of infliximab and not a result of worsening of the disease course.…”
supporting
confidence: 93%
“…Furthermore, Olivieri et al reported 2 successful cases of the use of infliximab in relieving chest wall pain and pustulosis [6]. Massara et al reported 4 cases of osteoarticular manifestations improvement after regular use of infliximab, though skin lesions aggravated, which was then relieved by topical steroids [5]. Palmoplantar pustulosis also relapsed in our case during entercept therapy, but the symptom self-improved without treatment interruption.…”
Section: Discussionmentioning
confidence: 60%
“…Entercept and infliximab, the two TNF-a blocking agents, have been reported to be effective in treating SAPHO syndrome [1,4,5]. Wagner et al reported 2 cases that after entercept and infliximab are added following uneventful NSAIDs and DMARDs treatment, the patient's conditions improved.…”
Section: Discussionmentioning
confidence: 99%